Using English Language Teaching Professionalism to Bash Cultural Imperialism in the Sultanate of Oman: A Response to Wyatt and Sargeant. Issue 3 (3rd July 2021) - Al-Issa, Ali
ABSTRACT: Historically and as a developing country, the Sultanate of Oman has always been culturally dependent on Britain to plan and implement its English Language Teaching (ELT) and in-service teacher education. This dependency has negatively affected preparing English language teachers with a new global professional identity capable of introducing change to the Omani ELT system. This argument is at the heart of my response to Wyatt and Sargeant's article in this issue of Changing English . I argue for professionalism as a political ideology capable of resisting and challenging the ELT cultural imperialism.